Patient-Reported Long-Term Outcome is Superior After Treatment with Self-Expanding Metallic Stents in Esophageal Perforations. (June 2021) - Waltersten, M.; Sundbom, M.
Background and aims: Esophageal perforations are life threatening. Since the 1990s, placing of covered esophageal stents has become an alternative to surgery. Theoretically, this minimally invasive approach has several benefits; however, little data are available on long-term outcome in these patients. We aimed to evaluate how patient-reported outcome differed between full surgery and placement of self-expanding metallic stents when treating primary benign esophageal perforations. Material and methods: Of 48 patients treated at our hospital in 2000–2015, 23 were alive and asked to answer three questionnaires. We used a short clinical questionnaire, the QLQ-OG25 from the European Organization for Research and Treatment of Cancer and a simplified quality-of-life instrument, the Check Your Health. Non-parametric statistics were used to evaluate differences between the two groups. Results: In all, 20 (87%) individuals (13 men, 64 years of age) responded. At survey, surgical patients had lost 13 kg of initial weight, compared to no weight loss in the self-expanding metallic stents group (p = 0.01). This involuntary weight loss worried patients according to the QLQ-OG25; otherwise patient-experience measures did not differ between groups. For quality of life, surgical patients scored significantly lower physical health, emotional well-being, social functioning, and overall quality of life after treatment, but after stenting no differences were seen. Conclusions: In contrast to stenting, surgical treatment was associated with involuntary, and worrisome, weight loss as well as reduced quality of life. We therefore believe that self-expanding metallic stents should be used when possible in treating benign esophageal perforations.